Hormonal therapy for aging process in women - Ganis Siregar, Muhammad Fidel Ganis (International Journal of Advances in Medicine, 2017)
Aging is a natural process that continues over time. This process beginswith fertilization and experienced by all living things, with different manifestation between each person. Since time immemorial, mankind has been concerned with the development and maintenance of their youth, slowing the aging process, and prolonging life. Currently, there are major advances for understanding the aging process in an attempt to delay it. Some scientific literature shows that supplementation with hormones such as estrogen, progesterone, testosterone, growth hormone, and thyroid hormones have the potential to improve the quality of life and prevent many symptoms and conditions associated with aging, including fatigue, depression, weight gain, weakness, osteoporosis, loss of libido, and cardiovascular disease. There are doubts about the side effects of long term use of hormonal therapy, including increased risk of cancer. Because hormone levels declines with aging, hormone treatment has been referred to as the "fountain of youth”. Many studies were conducted to prove the efficacy of hormonal therapy, but only partial data has shown the expected positive effects of the hormone on aging.